Pengaruh Kepemilikan Manajerial dan Kebijakan Dividen terhadap Nilai Perusahaan - Anita, Aprilia; Yulianto, Arief (Management Analysis Journal, 2016)
The purpose of this study was to examine the effect of managerial ownership and dividend policy on firm value (the study is a manufacturing company that is listed on the Indonesia Stock Exchange in 2010 until 2013). The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2010 until 2013. Samples were taken purposive sampling technique that is based on specific criteria. Data analysis tools used in this research is descriptive analysis and multiple linear regression analysis. The results obtained multiple linear regression analysis Y = 0.855 + 2.797 - 0.004 + e. The results of the simultaneous test (F test) showed managerial wnership and dividend policy jointly affect firm value. Managerial ownership effect on firm value. Dividend policy is no effect on firm value. The conclusions of this research is managerial ownership effect on firm value. Dividend policy is no effect on firm value. Advice given to the owner/shareholders of the companies to increase managerial ownership and dividend policy in order to reduce the agency conflict.